The transition from “fantastic reality” to the “realistic fantasy” in the 1990s and the novel as practice –Rereading Kim Young-ha’s “Jeon Tae-il and Showgirl” - Lee, Seong-Ah (International Journal of Korean Humanities and Social Sciences, 2025)
A perspective that seeks to understand ‘what a novel does’ before asking ‘what a novel means’ stems from a will to deconstruct the notion of a transcendental reality. This will reveals that a novel is not simply ‘about’ something, but that it ‘constitutes’ something producing new meaning by communicating with the external world. In this way, the literary scene of the 1990s serves as a suitable experimental ground for a perspective that focuses on the novel’s performativity, as it was a time and space where the conceptual frameworks once considered representations of reality were lost. While an amorphous reality and inner self are constructed alongside the process of writing, the contradiction that serves as the foundation for the existence of the subject of authenticity persists. Therefore, as a part of a project to sketch a big picture of how the (im)possibility of forming a subject of authenticity in the 90s is realized through the novel, this paper focuses on Kim Young-ha’s novels. His novels reveal an internal motility through a cognitive shift: moving from viewing reality fantastically to the recognition that reality itself is a fantasy – that is, from ‘fantastic reality’ to ‘realistic fantasy’. Based on this understanding, “Jeon Tae-il and Showgirl” gains the possibility of being read anew, freed from its initial interpretation as a mere reflection of its era. Through the montage-like insertion of advertisements, this novel doesn't just reflect a reality controlled by capitalism. It creates a reality as another form of virtuality by embodying the fantasy of advertising. Within this fantasy, attempts to deconstruct the dichotomous perception that gives rise to conflict are repeated. In this way, a moment is captured in which the novel’s immanence and transcendence resonate to produce meaning.